2020
DOI: 10.21203/rs.3.rs-27364/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LncRNA SNHG12 promotes proliferation and migration of vascular smooth muscle cells via targeting miR-766-5p/ EIF5A

Abstract: Background Although lncRNAs have reported to serve as potential biomarkers of atherosclerosis (AS), the role of lncRNA SNHG12 in AS are still unknown. Methods In present study, we investigated the regulatory effects of SNHG12 on human vascular smooth muscle cells (hVSMCs). RT-qPCR were employed to determine the expressions of SNHG12, miR-766-5p and eukaryotic translation initiation factor 5A (EIF5A). Cell viability was estimated via the Cell Counting Kit-8 assay. Wound healing and Transwell invasion assays wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Another study showed that lncRNA MCM3AP-AS1 enhances the expression of eIF4E by acting as a sponge for miR15a, which supresses eIF4E expression and contributes to doxorubicin resistance in Burkitt lymphoma cells through MCM3AP-AS1/miR-15a/eIF4E axis [ 67 ]. Similarly, lncRNA SNHG12 enhanced the invasion of human vascular smooth muscle cells by serving as a sponge of miR-766-5p and influencing the miR-766-5p/eIF5A axis [ 68 ]. In the other study, a Y-linked lncRNA, LINC00278, was found to encode a micropeptide called YY1BM which led to a decrease in the expression of negative regulator of translation, eEF2K [ 69 ].…”
Section: Acting Mechanisms Of Lncrnas In the Regulation Of Translamentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that lncRNA MCM3AP-AS1 enhances the expression of eIF4E by acting as a sponge for miR15a, which supresses eIF4E expression and contributes to doxorubicin resistance in Burkitt lymphoma cells through MCM3AP-AS1/miR-15a/eIF4E axis [ 67 ]. Similarly, lncRNA SNHG12 enhanced the invasion of human vascular smooth muscle cells by serving as a sponge of miR-766-5p and influencing the miR-766-5p/eIF5A axis [ 68 ]. In the other study, a Y-linked lncRNA, LINC00278, was found to encode a micropeptide called YY1BM which led to a decrease in the expression of negative regulator of translation, eEF2K [ 69 ].…”
Section: Acting Mechanisms Of Lncrnas In the Regulation Of Translamentioning
confidence: 99%
“… The mechanisms of action of lncRNAs on the regulation of cancer-related protein translation [ 31 , 34 , 35 , 38 , 64 , 67 , 68 , 82 , 84 , 85 , 86 , 87 , 148 , 151 , 153 ]. …”
Section: Figurementioning
confidence: 99%